From Hoax as Crisis to Crisis as Hoax: Fake News and Information Disorder as Disruptions to the Discourse of Renewal (Journal of International Crisis and Risk Communication Research, 2019)
Hoaxes have long been a reputational threat to organizations. For example, false claims that syringes had been found in bottles of Pepsi-Cola products, that a portion of a fi nger had been found in Wendy’s chili, and that Domino’s employees had intentionally served contaminated food to customers have topped the media’s agenda. More recently, the hoax phenomenon has been tactically reversed. Heavily traffi cked Internet sites and controversial television personalities frequently argue that well-documented crises themselves are hoaxes. The potential for claims of crisis as hoax to disrupt the discourse of crisis renewal is examined through an analysis of three cases. We argue that overcoming such disruptions requires corporate social responsibility, a focus on the issues rather than the hoaxers, and continued eff orts to improve media literacy for all audiences.